LGR-5 sebagai Biomarker pada Kanker Kolorektal: Tinjauan Sistematis Fitur Klinikopatologis dan Nilai Prognostik: Analisis - Aiman Hilmi Asaduddin; Roisya Nur Farhania; Namira Putri Imani; Cindy Ayudia Pramaesti; Andayani Yuwana Sari (Cermin Dunia Kedokteran, 2025)
Colorectal cancer (CRC) had the third highest cancer incidence worldwide. Recent researches are targeting specific gene expression as CRC marker. Leucine rich repeat-containing G-protein coupled receptor 5 (LGR5) is one of the genes that regulate tumor metastasis and growth. The aim of this study is to explain the correlation between LGR5, clinical pathology, and prognosis of CRC. This systematic review was arranged using PRISMA for eligible cohort studies and evaluated using Newcastle-Ottawa scale. From 63 articles, 6 articles were selected as eligible articles for data extraction and evaluation. Based on the studies, LGR5 positivity was positively associated with histopathological characteristics, TNM staging, and vascular invasion. Besides, LGR5 expressions in those studies were high and could be positively detected by this marker. LGR5 regulates Wnt/β-catenin signaling pathway promotion in normal colon stem cell. Methylation of Wnt target gene promoter is potent predictor to CRC recurrence thus the expression of LGR5 can be used as CRC marker. LGR5 plays a role as pro-oncogenic factor in colorectal carcinogenesis via prostaglandin E2 and Epidermal Growth Factor signaling. LGR5 induction also could increase cancer cells chemoresistant ability. Thus, LGR5 could determine prognosis of CRC patient and were related to certain clinicopathological features and tumor progressions.